Studi Fenomenologi Unpaid Intership di Kalangan Mahasiswa Universitas Singaperbangsa Karawang - Septiyana Monica, Ginna; Yanti Tayo; Wahyu Utamidewi (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Entering the world of work, one of the important steps that every individual must go through is to take part in an apprenticeship program. Training is conducted in a work environment with direct instructor guidance and supervision through an integrated training system. This research uses a qualitative method with a phenomenological approach. The theory used in this research is Alfred Schutz's phenomenological theory. The subjects in this study amounted to four resource persons selected based on certain criteria, namely students of Singaperbangsa University of Karawang who had participated in unpaid intership activities. Data collection techniques used were in-depth interviews, observation, and literature study. The purpose of this study was to determine the motives, meanings, and communication experiences of Singaperbangsa Karawang University students participating in unpaid intership activities. The results stated that there were several motives, meanings and communication experiences known from each informant. There are two motives, the first is the cause motive, which is due to an obligation to fulfill courses and work systems and affordable scope. Second, the purpose motive is to increase self-potential. The meaning obtained is that informants think that it is okay to take part in unpaid internships as long as they know their own capacity and do not harm themselves. And the experience of participating in unpaid internship activities as a means of learning how to work, learning how to work, and learning how to work